(untitled) (Vietnam Journal of Community Medicine, 2025)
Objective: To evaluate the effectiveness and feasibility of the online reminiscence therapy library model for elderly people in nursing homes. Methods: An interventional study was conducted at Co Do Nursing Home (Can Tho) from October 15, 2023 to May 28, 2024, involving eight older adults with MMSE scores ≥ 19. An online reminiscence therapy library was developed using images and videos reflecting the life and people of Vietnam across different periods, based on the model of the Japanese Reminiscence Library. Each participant attended 16 themed reminiscence sessions (60 minutes per session). Pre- and post-intervention assessments included MMSE, the Zarit Burden Interview (ZBI), CERAD memory tests, and a satisfaction survey. Results: MMSE scores improved from 22.4 to 25.4 (increase 13.4%). ZBI scores decreased from 32 to 22 (decrease 31.25%). CERAD scores showed increases in immediate recall (increase 35.2%), delayed recall (increase 21.6%), and delayed recognition (increase 9.4%). All participants rated the intervention as “very satisfied.” Open-ended feedback revealed that reminiscence elicited positive emotions and cultural and familial memories. Conclusion: The reminiscence therapy library model demonstrated effectiveness in enhancing cognition, memory, and mental well-being in older adults, while also reducing caregiver burden. This is a feasible model that could be scaled and integrated into long-term care systems amid Vietnam’s rapidly aging population.